(untitled) (Research, Society and Development, 2021)
The body self-image consists of the mental representation of one’s own body and, when it differs from the idealized one, it generates dissatisfaction. Considering the ideal beauty standards established by the media, individuals often suffer from excessive dissatisfaction, which can lead to self-image distortion and eating disorders. Therefore, this study sought to provide an overview of the influence of social media on body self-image and the occurrence of eating disorders, highlighting the role of the nutritionist in these cases. It can be observed that social media have a direct impact on body dissatisfaction, conveying the thin body as a synonym for status, success and sensuality, with greater emphasis on social networks. In this scenario, the most affected are women, especially teenagers, who undergo bodily changes during this period, are more exposed to the media and are more influenced. Cases of eating disorders, such as anorexia and bulimia nervosa, can develop and are constantly accompanied by a distorted self-image. Finally, it was possible to identify that the nutritionist, within a multidisciplinary treatment team, has a fundamental role, as he can act both in the diagnosis, by verifying changes, and in the treatment itself, through dietary re-education and other methodologies, being essential the specific knowledge of the topic.